A novel linearization approach of chord and twist angle distribution for 10 kW horizontal axis wind turbine. (November 2021) - Alkhabbaz, Ali; Yang, Ho-Seong; Weerakoon, A.H Samitha; Lee, Young-Ho
Abstract: In the present work, the aerodynamic design of a 10 kW horizontal axis wind turbine rotor is performed using both ideal and actual rotor theories. The obtained nonlinear blade profile is optimized in order to enhance the aerodynamic performance and to ease the fabricating complexity. A unique linearization approach is employed to linearize the chord and twist distribution by dividing the congruent line of both ideal and actual models into equal divisions. The points along the identical tangent line are considered as floating new blade roots, whereas the blade tip was kept fixed based on the primary design. The linear profile based on the new value of blade root is described using algebraic equations. The local element torque, capacity factor, and the annual energy production based on the Weibull distribution are adopted to determine and assess the optimal blade profile. Both CFD investigation and the FEA analysis are performed in order to evaluate both primary and optimized blades. The aerodynamic and aeroelastic comparison in terms of power output, thrust force, blade tip deflection, and the equivalent stress distribution of both blade profiles has been done over a wide range of incoming wind speeds. Results show an enhancement in the aerodynamic performance in terms of power coefficient up to (5.9%) compared to the primary blade design. Moreover, the optimized blade has shown less tip deflection by 27.92% than the primary blade at low wind speed. Highlights: □ An innovative linearization approach of the chord and twist angle distributions is proposed. □ The CFD and FEA analysis are conducted for both optimized and primary blade profiles. □ The power coefficient of the optimized blade has improved up to 5.9% compared to the primary design. □ The optimized blade shows less tip deflection by 27.92% compared to the primary blade.